Culture, suicide, and the human condition - Honkasalo, Marja-Liisa; Tuominen, Miira (New York : Berghahn Books, 2014)
Suicide is a puzzling phenomenon. Not only is its demarcation problematic but it also eludes simple explanation. The cultures in which suicide mortality is high do not necessarily have much else in common, and neither is a single mental illness such as depression sufficient to lead a person to suicide. In a word, despite its statistical regularity, suicide is unpredictable on the individual level. The main argument emerging from this collection is that suicide should not be understood as a separate realm of pathological behavior but as a form of human action. As such it is always dependent on the decision that the individual makes in a cultural, ethical and socio-economic context, but the context never completely determines the decision. It also argues that cultural narratives concerning suicide have a problematic double function: in addition to enabling the community to make sense of self-inflicted death, they also constitute a blueprint depicting suicide as a solution to common human problems.
Introduction: varieties of suicide: inquiring into the complexity of human experience / Marja-Liisa Honkasalo and Miira Tuominen. PART I: SUICIDE: CROSS-CULTURAL PERSPECTIVES. 1. The construction of the suicidal self in phenomenological psychology / Charles J.-H. Macdonald and Jean Naudin. 2. When it is worth the trouble to die: the cultural valuation of suicide / María Cátedra. PART II: ANCIENT AND MEDIEVAL APPROACHES TO SUICIDE. 3. "Tell him to follow me as quickly as possible": Plato's Phaedo (60c - 63c) on taking one's own life / Miira Tuominen. 4. Free philosophers and tragic women: Stoic perspective on suicide / Malin Grahn. 5. Moral philosophical arguments against suicide in the Middle Ages / Virpi Mäkinen. PART III: MORALITY, POLITICS, AND VIOLENCE: SUICIDE IN CONTEMPORARY SOCIETIES. 6. "She kissed death with a smile": the politics and moralities of the female suicide bomber / Susanne Dahlgren. 7. "When we stop living, we also stop dying": men, suicide, and moral agency / Marja-Liisa Honkasalo. Afterword / Arthur Kleinman.
Julkaistu myös verkkoaineistona.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Suicide -- Philosophy; Suicide -- Social aspects; filosofi; filosofia; itsemurha; kulttuuri; kultur; självmord; sociologi; sosiologia